The evolution of psychotherapy: from Freud to prescription digital therapeutics - Docherty, John P.; Colbert, Brett M. (Frontiers in Psychiatry, 2024)
The evolution of psychotherapeutic treatments from Freud to digitally administered evidencebased treatments reflects a history of progressive advance. This history is characterized by identification of problems with the current state of the art, followed by solutions inspired and supported by advances in basic science and technology leading to subsequent recognition of other limitations revealed by the new advance. The common thread running through this process is (a) increasing specificity of the psychotherapeutic interventions, (b) increasing evidence of efficacy and safety, (c) increasing integrity and reliability in the delivery of the intervention, (d) increased equality of access, and (e) recognition of the need for regulation to provide protection for the public from unsafe or ineffective products. This evolution of psychotherapeutic treatments, not surprisingly, has been foreshadowed by the precursor history of the evolution of pharmacologic treatment.Although intellectual history is lumpy and does not sort itself into discrete and coherent epochs, such sorting is a useful heuristic for describing the advance of medicine and the therapeutic enterprise. This paper will discuss six successive epochs of psychotherapy. For each it will discuss the problem of the preceding era it sought to solve, the advance it brought to the field, the emerging science and technology that supported that advance, and the precursor development in pharmacological treatments that foreshadowed that epoch of psychotherapy.Finally, it will conclude with some observations about the proximate future.